Multiple Site Cryoablation Treatment of the Posterior Nasal Nerve for Treatment of Chronic Rhinitis: An Observational Feasibility Study. (August 2020) - M. Yen, David; B. Conley, David; O'Malley, Ellen M.; Byerly, Tracy A.; Johnson, Jacob
Background: Cryoablation of the posterior nasal nerve at the middle meatus has been shown to successfully treat nasal obstruction and symptoms of chronic rhinitis. Cryoablation of both the middle and inferior meatus has not yet been studied. Objectives: To evaluate the safety and feasibility of cryoablation of the posterior nasal nerve at both the middle and inferior meatus locations to treat chronic rhinitis. Methods: Participants underwent bilateral cryoablation of the posterior nasal nerve at both the middle meatus and inferior meatus and were assessed through 3 months post treatment. The primary endpoint is the change from baseline to 3-month follow-up in the reflective Total Nasal Symptom Score (rTNSS). Other assessments include additional patient-reported outcomes, physician assessment, and independent review and scoring of imaging. Results: Thirty participants were enrolled at 3 US centers. There was a significant improvement from baseline in the median rTNSS (–4.0, P  < .001) at 3 months. Statistically significant improvements from baseline ( P  < .001) were also observed with the Nasal Obstruction Symptom Score (NOSE), nasal symptom visual analog scale (VAS), Sino-Nasal Outcomes Score (SNOT-22), and mini Rhinoconjunctivitis Quality of Life Questionnaire (mini RQLQ). Clinical Global Impression – Improvement (CGI-I) indicated that 89.7% (26/29) of participants experienced improvement at 3 months. No serious adverse events were reported. Conclusion: Cryoablation at both the middle meatus and inferior meatus appears to be a safe and feasible option for treatment of chronic rhinitis. In this feasibility study, there is significant improvement in symptoms post treatment. Adverse events are minor and transient.